IMPLEMENTASI AKAD MURABAHAH SEBAGAI AKAD PEMBIAYAAN KEPEMILIKAN LOGAM MULIA PADA PEGADAIAN SYARIAH CABANG PALU - Uswatun Hasanah (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2016)
Precious metals investment is still regarded as the safest investment, other than because its value is stable is also regarded as the instrument that never timeless. But for some people, the desire to invest in precious metals can not be realized because they do not have enough funds. However, these constraints currently not be a problem anymore, because the Islamic pawnshop has been providing mortgage financing of precious metals.